Lateral flow immunoassay strips based on europium(III) chelate microparticle for the rapid and sensitive detection of Trichinella spiralis infection in whole blood samples of pigs - Wang, Xinyu; Li, Aizhe; Wang, Ruizhe; Hou, Tianji; Chen, Huixin; Wang, Jing; Liu, Mingyuan; Li, Chen; Ding, Jing (Frontiers in Cellular and Infection Microbiology, 2022)
Trichinellosis is a major food-borne parasitosis caused by ingesting raw or semi-raw meat products from pigs infected with Trichinella spiralis (T. spiralis). Although China is the largest consumer of pork in the world, the current diagnostic method of T. spiralis is exclusively performed in a laboratory setting, due to its complexity and laborious procedure. Here, in order to solve the detection problems in the pig breeding industry, a rapid, sensitive, and on-site serological diagnosis method was developed. The novel lateral flow immunoassay strip (ICS) is based on europium(III) chelate microparticle (ECM) to detect T. spiralis-specific IgG antibody in the serum and whole blood samples from pigs. The structure of the blood-filtering pad and the conjugate pad was added to the ICS, allowing for whole blood samples to be detected and enabling on-site deployment. By comparing the detection results of the serum samples and the whole blood samples, the detection limit of this method was evaluated. Thereafter, this method was used to investigate Trichinella infection in Chongqing, Sichuan, Inner Mongolia, Guangxi, and Liaoning provinces of China, and the results were almost consistent with the standard method of artificial digestion. Taking advantage of its user-friendly procedure, short detection time (3 min), and sensitivity, the ECM-ICS could be employed for monitoring the epidemic of Trichinella infection and ensuring meat safety.